Neuroanatomy, episodic memory and inhibitory control of Persian-Kurdish simultaneous bilinguals - Samira Golshani; Olga Kepinska; Hamid Gholami; Narly Golestani (Scientific Reports)
Abstract We assessed simultaneous bilinguals and monolinguals on inhibitory control and episodic memory, and assessed their grey matter volumes in brain regions known to be involved in language processing, executive control and memory. Bilinguals outperformed monolinguals on episodic memory, and performance on the memory and inhibition tasks were correlated, only in the bilingual group. This suggests that the bilingualism-related benefits on memory are related to individual differences in executive control. We found larger grey matter volumes in bilinguals in left pars opercularis and in bilateral SFG, caudate nuclei, and parasubiculum. Episodic memory performance was correlated with volumes of bilateral posterior hippocampi, again only in the bilinguals, again suggesting that bilingualism may be driving this effect. Finally, we found positive structural covariance between the volumes of the bilateral parasubiculum and that of important components of the executive control network. We provide a novel, mechanistic explanation accounting for observed behavioural advantage and brain structural differences: bilingualism may boost the prefrontal cortex-hippocampal neural circuitry commonly underlying both executive control and memory, via cascade and reverberant effects, leading to synergistic benefits in both cognitive domains. This new framework has important implications for protective effects on cognition and brain health in relation to second language learning.